Efeitos de diluição química no composto intermetálico GdIn3 - Silva, Leonardo de Sousa (2013)
This work proposes the development of a technique to growth of single crystals through metallic flux technique at the Sergipe State. Besides, the system YxGd1-xIn3 (0 x 0.5 to pass of 0.10 % ) has been obtained via this technique and its structural and magnetic properties are studied. X-ray diffraction results have been performed in order to verify if the desired crystalline phase was obtained. The experimental results show that it has been grown with success. The magnetic characterization is carried out through magnetic susceptibility data as function of temperature (2 x 300 K) and magnetic field (??7 H 7T). The T-dependence of the magnetization shows a suppression of the magnetic ordering temperature with increasing of the yttrium concentration. The analyses of these experimental data show that the system presents magnetic frustration which is linked to the dilution effect introduced by the yttrium ion in the gadolinium site. The magnetization data as function of magnetic field carried out at 2 K show a usual behavior of a material with antiferromagnetic ordering.